2021
DOI: 10.1159/000514168
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Effect of Two Fluoride Varnishes in Caries-Active Preschool Children: A Randomized Controlled Trial

Abstract: The prevention of dental caries in preschool children is a priority for dental services. The aim of the study was to investigate the caries-preventive effect of 2 fluoride varnishes in caries-active preschool children, and then compare the outcome with a non-varnish control group. After screening, 180 preschool children aged 36–71 months, with at least 1 noncavitated lesion, were enrolled and randomly allocated into 3 parallel groups, namely A: 1.5% ammonium fluoride varnish (Fluor Protector S), B: 5% NaF varn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“… 43 , 44 Fluoride varnishes were also reported as effective compounds to prevent the development of early caries lesions in both primary and permanent teeth. 43 , 44 , 45 , 46 , 47 The caries-arresting potential of these varnishes, however, were mainly restricted to ICDAS 1-3 lesions rather than to active dentin lesions, where SDF achieves higher CAR percentages.…”
Section: Resultsmentioning
confidence: 99%
“… 43 , 44 Fluoride varnishes were also reported as effective compounds to prevent the development of early caries lesions in both primary and permanent teeth. 43 , 44 , 45 , 46 , 47 The caries-arresting potential of these varnishes, however, were mainly restricted to ICDAS 1-3 lesions rather than to active dentin lesions, where SDF achieves higher CAR percentages.…”
Section: Resultsmentioning
confidence: 99%
“…The search for new solutions motivated us to prove the possibility of choosing a means/method for preventive treatment of the initial carious lesions, with the local application of fluorides [26]- [28]. It is necessary: To carry out a timely and early diagnosis to cover the carious lesions in their early phase, applying preventive and non-invasive treatment, which saves time, and pain and protects the child from complicated caries.…”
Section: Discussionmentioning
confidence: 99%
“…In this 12-month randomized clinical trial, the efficacy of neutral fluoride gel was shown to be similar to that of the varnish. Studies have reported that the use of varnish applied two to four times a year can reduce the incidence of ECC, 14,18 and this reduction could could be as high as 25% when compared with a placebo. 18 However, some clinical trials have shown no benefits in using fluoride varnish to reduce the incidence of caries in preschool children regardless of whether they were exposed 9,10,19 to fluoridated water and/or fluoridated toothpaste, or not.…”
Section: Discussionmentioning
confidence: 99%
“…20 T he World Hea lt h Orga n i zat ion (WHO) recommends two to four fluoride applications a year in children at high risk for caries, 1 but this frequency may not be effective in controlling ECC. 21 The contradictory results in the literature 9,10,14,18,20 can be explained by the methodological differences between studies, such as the heterogeneity of patients in presence or absence of caries at baseline and the interval between varnish applications. In the present study, the incidence of caries was higher in children with ECC at baseline than in children without caries, corroborating the findings of another study 9 and consistent with previous experience that caries is an important predictor of the occurrence of new lesions 6 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation